Effect of Different Vitamins against Alternaria arachidis Kul. - B.M. Kareppa2, D.C. Kamthane1* and (Recent Research in Science and Technology, 2011)
Among oil seed crops, groundnut (Arachis hypogea L.) is an important crop. The underground as well as the foliar parts get affected by different micro-organisms causingÃ‚Â various diseases. Along with earlier known foliar disease, a new disease Alternaria Blight has been observed in the field. The alternaria blight infected leaves show marginal necrosis and increases inward to form wedge shaped lesions. The lesions get surrounded by yellow zone. The disease is increasing gradually year after the year. Therefore its study is essential. Alternaria arachidis Kul. causing alternaria blight was isolated & purified. DSI was increasing year after the year indicating that the disease occurrence is increasing and it needs control measures. The effect of different vitamins against Alternaria arachidis Kul. was studied. The different vitamins used for the study were as ascorbic acid, biotin, inositol, nicotinic acid, pyridoxine, riboflavin and thiamin. The concentration of these vitamins used was 0.25%. It was noted that ascorbic acid, biotin, nicotinic acid, pyridoxine and riboflavin were stimulatory while inositol and thiamine were inhibitory to the pathogen as compaired to the control.